DENR promotes translation reinitiation via ribosome recycling to drive expression of oncogenes including ATF4 - Bohlen, Jonathan; Harbrecht, Liza; Blanco, Saioa; Clemm von Hohenberg, Katharina; Fenzl, Kai; Kramer, Günter; Bukau, Bernd; Teleman, Aurelio A. (Nature Communications, 2020)
Translation efficiency varies considerably between different mRNAs, thereby impacting protein expression. Translation of the stress response master-regulator ATF4 increases upon stress, but the molecular mechanisms are not well understood. We discover here that translation factors DENR, MCTS1 and eIF2D are required to induce ATF4 translation upon stress by promoting translation reinitiation in the ATF4 5′UTR. We find DENR and MCTS1 are only needed for reinitiation after upstream Open Reading Frames (uORFs) containing certain penultimate codons, perhaps because DENR•MCTS1 are needed to evict only certain tRNAs from post-termination 40S ribosomes. This provides a model for how DENR and MCTS1 promote translation reinitiation. Cancer cells, which are exposed to many stresses, require ATF4 for survival and proliferation. We find a strong correlation between DENR•MCTS1 expression and ATF4 activity across cancers. Furthermore, additional oncogenes including a-Raf, c-Raf and Cdk4 have long uORFs and are translated in a DENR•MCTS1 dependent manner.